2009
DOI: 10.1159/000236001
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 in Human Eosinophils: Functional Effects and Decreased Expression during Allergic Rhinitis

Abstract: Background/Aim: Viral respiratory infections are increasingly implicated in allergic exacerbations. Virus-induced activation of eosinophils through Toll-like receptors (TLRs) could be involved. The present study was designed to examine TLR3 expression in eosinophils from bone marrow (BM) and peripheral blood (PB) during symptomatic allergic rhinitis, and to evaluate the functional responsiveness of TLR3 in purified eosinophils. Methods: BM and PB samples were obtained from healthy volunteers and patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 74 publications
0
28
0
Order By: Relevance
“…These 17 SNPs comprise 2 on TLR1, 4 on TLR2, 2 on TLR4, 3 on TLR6, 1 on TLR7, 2 on TLR8, 1 on TLR9, and 2 on TLR10. Although expressions of TLR3 and TLR5 have been linked with allergic rhinitis34 and asthma,36 none of the SNPs on TLR3 and TLR5 has been shown to be associated with allergic diseases.…”
Section: Tlr Snps and Allergic Diseasesmentioning
confidence: 99%
“…These 17 SNPs comprise 2 on TLR1, 4 on TLR2, 2 on TLR4, 3 on TLR6, 1 on TLR7, 2 on TLR8, 1 on TLR9, and 2 on TLR10. Although expressions of TLR3 and TLR5 have been linked with allergic rhinitis34 and asthma,36 none of the SNPs on TLR3 and TLR5 has been shown to be associated with allergic diseases.…”
Section: Tlr Snps and Allergic Diseasesmentioning
confidence: 99%
“…Furthermore, Mansson and colleagues stated that expression of TLR7 and TLR9 was the same between healthy and atopic patients. However, upon in vitro TLR stimulation with R-837 (TLR7) or CpG (TLR9), eosinophils from atopic patients had increased cytokine production and granule protein secretion compared to those from healthy patients [17]. These data suggest that important differences exist between these two conditions (atopic vs. healthy status) and immunological environments [17].…”
Section: Pathogen Recognition By Eosinophilsmentioning
confidence: 99%
“…However, upon in vitro TLR stimulation with R-837 (TLR7) or CpG (TLR9), eosinophils from atopic patients had increased cytokine production and granule protein secretion compared to those from healthy patients [17]. These data suggest that important differences exist between these two conditions (atopic vs. healthy status) and immunological environments [17]. It is important to consider these observations, as they may explain some of the discrepancies regarding specific TLR expression and subsequent activation of eosinophils.…”
Section: Pathogen Recognition By Eosinophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Szczeklik1 has hypothesized that AERD develops as the result of chronic viral infection. Recently, it has been shown that eosinophils activated via Toll-like receptor 3 (TLR3) might be more able to recruit leukocytes to sites of inflammation, and that eosinophils might function as a link between viral infection and exacerbation of allergic disease 2. Viral respiratory infections have been suggested to contribute to allergic sensitization and development of asthma, and in subjects with already established asthma, they are known to exacerbate the allergic disease 3.…”
Section: Introductionmentioning
confidence: 99%